Ironmaking and Steelmaking Processes Greenhouse Emissions, Control, and Reduction - Cavaliere, Pasquale; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book describes improvements in the iron and steel making process in the past few decades. It also presents new and improved solutions to producing high quality products with low greenhouse emissions. In addition, it examines legislative regulations regarding greenhouse emissions all around the world and how to control these dangerous emissions in iron and steel making plants. .
Part I Sintering Plants Operations -- 1 Sinter Plant Operations: Raw Materials -- 2 Predictions of PCDD/F, SOx, NOx and Particulates in the Iron Ore Sintering Process of Integrated Steelworks -- 3 Dangerous emissions reduction in sintering plants -- 4 Pollutants Emission and Control for Sintering Flue Gas -- 5 Sinter Plant Operations: Hazardous emissions -- Part II Blast Furnace Operations -- 6 Recent Trends in Ironmaking Blast Furnace Technology to Mitigate CO2 Emissions Top Charging Materials -- 7 Dangerous emissions in blast furnace operations -- 8 Mathematical Simulation of Blast Furnace Operation -- 9 CO2 emissions reduction in Blast Furnaces -- 10 Recent Trends in Ironmaking Blast Furnace Technology to Mitigate CO2 Emissions Recent Trends in Ironmaking Blast Furnace Technology to Mitigate CO2 Emissions -- 11 Low CO2 emission by improving CO utilization ratio in China's blast furnaces -- Part III Electric Arc Steelmaking -- 12 Dioxins emissions control in Electric Arc Furnaces for Steel Production -- 13 Emission of high toxicity airborne pollutants from electric arc furnaces during steel Production -- 14 Use of Sustainable Inorganic Binders in the Treatment of Bag-House Dust -- 15 Dangerous Emissions during Steelmaking in Electric Arc Furnaces (EAFs) -- 16 Electric Arc Furnace -- Part IV Greenhouse emissions -- 17 Waste Materials recycling in Steelmaking operations -- 18 Pollution Air Control in Sinter Plants -- 19 Risk Assessment and Control of Emissions from Iron and Steelmaking -- 20 CO2 Emission in China's Iron and Steel Industry -- 21 Recent progress and future trends of CO2 breakthrough iron and steelmaking technologies for CO2 mitigation -- 22 Manganese emissions from steelmaking -- 23 Potential of best available and radically new technologies for cutting carbon dioxide emissions in ironmaking -- 24 Greenhouse Gas Emissions and Energy Consumption of Ironmaking Processes. .
Keywords: Metals; Manufactures; Metals and Alloys; Machines, Tools, Processes